METHODOLOGICAL APPROACHES TO THE DEVELOPMENT OF MECHANISMS FOR THE SYSTEM INTEGRATION OF AGRICULTURAL, PROCESSING AND MARKETING ENTERPRISES - Anna Aleksandrovna LEKSINA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
System integration can be an economically advantageous tool for increasing the competitiveness of the regional agro-industrial complex. The article substantiates a methodological approach to the development of mechanisms for the system integration of agricultural, processing and marketing enterprises, reflecting the views of international and national standards of the Russian Federation. This is a three-stage structured algorithm for constructing elements of functional, informational, organizational and resource subsystems and the relationships between them. At the first stage, the system integration of internal functions and processes of the enterprise is carried out. At the second stage, elements are allocated for the formation of subsystems in the process of combining objects. At the third stage, mechanisms for the functioning of subsystems are built on the basis of mutual interest in the development of integrated objects. The mechanisms form and provide both internal and external inter-economic interaction, movement and synchronization of the flows of the totality of information and resources of the organizations under study. A comprehensive methodology for evaluating system integration performance indicators is presented, including quantitative and qualitative characteristics of five hierarchical levels.